Importance of Environmental Education As Perceived by Secondary School Students - Agnieszka PAWLUK- SKRZYPEK; Monika JUREWICZ (Communications of International Proceedings, 2024)
The main objective of the study was to analyse how environmental education is perceived by secondary school students. The research was carried out using the method of a diagnostic survey, where the technique of a questionnaire created on the SurveyLab was used. Two thematic areas were identified in the research: firstly, respondents' understanding of the term environmental education; secondly, environmental education for improving environmental quality as perceived by respondents. The analysis of the research material showed that, for the respondents, environmental education is teaching about ways to protect the environment and learning about the environment and nature. As the dominant source of knowledge in this area, the respondents primarily point to the Internet, which is also their preferred educational space. It should also be noted that a form of environmental education that seems to 'speak' well to those surveyed are social campaigns. The analysis of the data shows that the school and the traditional ways of teaching and traditional teaching aids in the form of books, textbooks or paper press are not attractive to the respondents, as can be seen from the low number of indications. Furthermore, parents and teachers are not a source of knowledge in this area for the respondents. In turn, the indications made by respondents suggest that conducting environmental education with the help of new media and social campaigns contribute to the effective promotion of environmental education knowledge. It can be assumed that this is related to the motivation of greater involvement, which becomes a cause for real action in this area.
Keywords: environmental education; secondary school students